The Role of Artificial Intelligence in Achieving the Quality of External Audit: An Exploratory Study from the Auditors’ Point of View in the Kurdistan Region of Iraq - حمە سعيد ڤيان سليمان; حمە حسين سەلار مهدی (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This research aims to identify the importance of using artificial intelligence techniques in achieving the quality of external audit in the Kurdistan Region, and to achieve this a questionnaire was designed and distributed to the study sample of 60 chartered accountants and auditors, 52 questionnaires were subjected to statistical analysis. After analyzing the questionnaire’s vocabulary by computer, and using the SPSS statistical analysis program, it was reached that there is an awareness among auditors and chartered accountants in the external audit offices in the Kurdistan Region / Iraq of the importance of using information technology in improving the quality of external audit services, and that the use of artificial intelligence technologies works on Improving the quality of the planning stage of the audit process, improving the auditor’s analytical procedures, and improving the quality of audit work and its documentation. The study also concluded that there is a role for expertise, training and technical knowledge in the use of information technology in audits in a positive impact on the quality of external audit. The researcher recommended the need for external audit offices, chartered accountants and auditors to use artificial intelligence techniques in implementing the procedures of the audit process, as well as the need to take practical training courses to enable and educate auditors on the importance of the actual use of information technology in auditing operations, and train them on how to use it.